Newtonianism: How Thomas Paine Devalued the British Monarchy by Transforming John Locke’s Empiricism and Social Contract Theory - Šklíbová, Jana (Univerzita Pardubice, 2016)
The article concerns Thomas Paine’s Newtonian concepts of society and government in the context of the Age of Enlightenment. Its aim is to demonstrate how Thomas Paine reinterpreted Enlightenment political thought as proposed by the empiricist theorist, John Locke, by using the principles of Newtonianism. Paine’s Newtonian politics is closely connected with his deistic faith. His political theory is devoted to the vision of a free society as a manifestation of the benevolent The Watchmaker. With this mission in mind, Paine attempted to devalue the contemporary models of the state of nature and social contract theory as interpreted by John Locke and to offer a more democratic version of these concepts. Paine’s key ideas in this respect are expressed in his most famous works Common Sense, The Rights of Man and The Age of Reason.
Newtonianismus: jak Thomas Paine znevážil britskou monarchii transformováním empirismu a teorie společenské smlouvy Johna Locka
Keywords: Thomas Paine; republic; society; government; Newtonianism; John Locke; Thomas Paine; republika; společnost; politické myšlení; osvícenství; vláda; Newtonismus; John Locke